THE COMPARISON OF CONCEPTS BETWEEN FUTUWWAH IN THE DISCIPLINE OF SUFISM WITH FITUA IN BIMA SUFISM EAST INDONESIA. - Hendrawangsyah, Hendrawangsyah; Omar, Syed Hadzrullathfi Bin Syed Omar (UIN Mataram dan Asosiasi Sosiologi Agama Indonesia (ASAGI), 2022)
The people of Bima only know Fitua as a tradition—which some Muslim groups use Fitua as a forum or space for interpreting Islamic values ??through religious philosophy discourse with one term